Efeito do tamanho da área nativa na reprodução de Trypoxylon (Trypargilum) lactitarse Saussure, 1867 (Hymenoptera: Crabronidae) - Oliveira, Grayce Kelly da Costa (2016)
Fragmentation of native vegetation implies in reduction of local species richness and abundance, increase the isolation of populations, leading to local species extinction. In fragmented areas, food and nesting resources for bees and wasps are unevenly distributed, which ultimately influences their foraging pattern behaviour, reproductive success, and survivorship. Thus, the aim of this study was to determine whether the size of areas of native vegetation remnants interferes with the reproductive success of a species of solitary wasp Trypoxylon lactitarse Saussure (1867), a recognized species of pollinator. Therefore, we set trap nests in the edges of different sizes forest fragments in the region of Goianápolis-GO, Hidrolandia-GO and surrounding municipalities. In these preexisting cavities, we quantified the foundation rate, the average number of cells with larvae, the survival of larvae, and adults hatched and size. In this work, the foundation rate was higher in larger fragments. However, the average number of cells per nest, the survival rate of larvae, and the size of the hatched adults did not differ between large and small areas. These results show that the size of the fragments may have higher influence on survival and retention of adults than in larvae.